2022
DOI: 10.18063/ijb.v9i1.631
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial nanocellulose-reinforced gelatin methacryloyl hydrogel enhances biomechanical property and glycosaminoglycan content of 3D-bioprinted cartilage

Abstract: Tissue-engineered ear cartilage scaffold based on three-dimensional (3D) bioprinting technology presents a new strategy for ear reconstruction in individuals with microtia. Natural hydrogel is a promising material due to its excellent biocompatibility and low immunogenicity. However, insufficient mechanical property required for cartilage is one of the major issues pending to be solved. In this study, the gelatin methacryloyl (GelMA) hydrogel reinforced with bacterial nanocellulose (BNC) was developed to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Mechanical stimulation is an effective means of promoting cartilage matrix secretion, which can affect the chondrocyte phenotype and alter the expression of extracellular matrix components, thereby enhancing the mechanical properties of the tissue building cartilage 24 . Zeng et al 25 developed GelMA hydrogels reinforced with bacterial nanocellulose (BNC), which significantly improved the mechanical properties of the hydrogels, enhanced cell migration and provided a mechanical environment for cartilage formation. Li et al 26 found that GelMA hydrogels with high stiffness (29.9 kPa) could better maintain cartilage development by preparing hydrogels with different stiffness.…”
Section: An Overview Of Gelmamentioning
confidence: 99%
“…Mechanical stimulation is an effective means of promoting cartilage matrix secretion, which can affect the chondrocyte phenotype and alter the expression of extracellular matrix components, thereby enhancing the mechanical properties of the tissue building cartilage 24 . Zeng et al 25 developed GelMA hydrogels reinforced with bacterial nanocellulose (BNC), which significantly improved the mechanical properties of the hydrogels, enhanced cell migration and provided a mechanical environment for cartilage formation. Li et al 26 found that GelMA hydrogels with high stiffness (29.9 kPa) could better maintain cartilage development by preparing hydrogels with different stiffness.…”
Section: An Overview Of Gelmamentioning
confidence: 99%
“…BNCenhanced compression resistance, cell migration, and ECM development promote cartilage maturation after implantation. 209 Carboxymethyl cellulose (CMC) is the FDA-approved anionic polysaccharide widely used as the viscosity modifier in bioprinting applications. 176,210−212 CMC has a good protein adsorption ability, mechanical rigidity, and slow degradation rate.…”
Section: Modulating Scaffold Properties Through Gelma Ink Modificationsmentioning
confidence: 99%
“…Zeng et al boosted bioink printability and mechanical strength (∼2 times) by reinforcing GelMA with BNC, enabling construction of an ear-shaped cartilage graft model for microtia patients. BNC-enhanced compression resistance, cell migration, and ECM development promote cartilage maturation after implantation …”
Section: Modulating Scaffold Properties Through Gelma Ink Modificationsmentioning
confidence: 99%
“…This similarity makes them ideal materials for creating a microenvironment that can aid in tissue repair and is an excellent candidate for biomimetic printing. The commonly used biomaterials in cartilage tissue engineering include gelatin [ 84 , 85 ], hyaluronic acid [ 86 , 87 ], alginate [ 88 , 89 ], collagen [ 90 ], silk protein [ 91 , 92 ], acellular extracellular matrix [ 93 , 94 ] and others [ [95] , [96] , [97] ]. However, these materials usually have to undergo fixed processing, such as decellularization and enzymatic hydrolysis, to remove immunogenicity and acquire printability, resulting in the destruction of some of their molecular structures and loss of their original physical properties.…”
Section: Bionic Materialsmentioning
confidence: 99%